Determinants of Electric Vehicle Purchase Intention among Cambodian Generation Z: An Integrated TAM–TPB Model - Chhayna Cheng; Sinoeurn Sok; Savry Sambath; Leangsean Va (jfpublisher, 2026)
As Generation Z (Gen Z) becomes an increasingly influential consumer segment, understanding their electric vehicle purchase intention is essential for businesses targeting this digitally native and environmentally conscious demographic. Although previous studies have applied the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB) to examine electric vehicle purchase intention, the two theories have been examined separately, with limited integrated SEM-based evidence in the Cambodian context. This study addresses the empirical research gap by integrating the TAM and the TPB into a cohesive framework to predict electric vehicle purchase intention among Cambodian Gen Z university students. Using a quantitative method, data were collected from 300 students across four faculties at BELTEI International University through structured questionnaires and analyzed with SPSS and AMOS. Exploratory factor analysis and confirmatory factor analysis were conducted to assess the factor structure and validity of the measurement model, while structural equation modeling was employed to examine the hypothesized relationships among constructs. The findings reveal that perceived ease of use significantly influences perceived usefulness, explaining 70% of its variance. Furthermore, perceived ease of use and perceived usefulness positively influence attitudes toward electric vehicle purchase, accounting for 68% of the variance in attitude. Finally, perceived ease of use, perceived usefulness, attitude, subjective norm, and perceived behavioral control significantly predict electric vehicle purchase intention, jointly explaining 79% of its variance. These results extend the TAM–TPB literature in a developing country context and offer practical insights for businesses and policymakers to promote electric vehicle adoption among Gen Z. Overall, future research may validate the model across broader populations and geographic settings.